Análise de biomarcadores de dor na saliva de pacientes diagnosticados com dor miofascial e submetidos ao tratamento cognitivo e fisioterápico - Flavia Fonseca Carvalho Soares (2017)
Myofascial pain is characterised by complex sensory, motor and autonomic symptoms caused by trigger points. It leads to pain, limited motion range and salivary flow decrease, impacting life quality. Cognitive and physiotherapy is a treatment modality for myofascial pain, aiming pain control and improvement on functional parameters of the temporomandibular joint. The effects of such therapy on salivary flow and salivary expression of pain mediators such as IL-6, IL-1, glutamate, substance P and ROS is unknown. We investigated the salivary flow rate together with salivary levels of IL-6, IL-1, substance P, glutamate and ROS in patients with myofascial pain before and during cognitive and physiotherapeutic treatment. Moreover, the association of pain intensity with the biomarkers concentration was also studied. Saliva of nineteen patients diagnosed with myofascial pain was collected before cognitive and physiotherapeutic treatment and during the treatment (04 and 08 weeks). No significant alteration of the expression levels of the biomarkers evaluated and the salivary flow rate throughout time was found. No correlation was found between pain intensity and the molecular parameters evaluated at any of the three moments. In conclusion, the biomarkers evaluated and salivary flow rates did not change during eight weeks of cognitive and physiotherapeutic intervention in the sample evaluated.